The Effect of Talent Management and Competence on Job Satisfaction and its Implication on Organizational Commitment at PT Sinergi Membangun Bangsa - Agus Setiawan Widio Saputro; Maswanto Maswanto; Nuraeni Nuraeni (Greenation Research & Yayasan Global Resarch National, 2023)
This study aims to examine the influence of talent management on job satisfaction, competence on job satisfaction, talent management on organizational commitment, competency on organizational commitment, job satisfaction on organizational commitment, talent management on organizational commitment through job satisfaction, competence on organizational commitment through satisfaction work. The research design used in this study is a quantitative and causal analysis method. The data came from 70 employees of PT Sinergi Membangun Bangsa through questionnaires and processed using the partial least squares (SmartPls). The results of this study simultaneously variable talent management and work competence affect job satisfaction with a contribution of 45,8%. Other than that, simultaneously talent management, work competence and job satisfaction affect organizational commitment, which is equal to 72,1%.